Pengembangan Prototipe Aplikasi Kurir Antarjemput Kotak Amal LazisMu Umbulharjo Menggunakan Metode User Centered Design - Tarmuji, Ali; Astuti, Nur Rochmah Dyah Puji; Anwar, Muhammad Dhabit (Forum Kerjasama Pendidikan Tinggi, 2021)
LazisMu Umbulharjo has quite a number of social activities, including raising funds through charity boxes to several points, such as places of worship, community services, and Muhammadiyah residents in the Umbulharjo area and its surroundings. LazisMu Umbulharjo has managed at least 900 charity boxes spread across 7 sub-districts of the Umbulharjo area and also outside the Umbulharjo area. Currently, the courier who shuttles the charity box is guided by the address that is packaged in a printed sheet that comes from Excel data. Some of the difficulties experienced by couriers when picking up charity boxes at these 900 points, among others, the large number of points that must be visited by one courier. Couriers have difficulty memorizing the positions of the hundreds of charity boxes. Courier difficulties and often missed on the way to the points of the charity box. Problems occur if the staff replaces them with new ones so that adjustments are made from scratch again in learning the pick-up location. This research was conducted based on the stages in the User Centered Design (UCD) process. Plan the human centered process, specify the context of use, specify user and organizational requirements, product design solutions, and evaluate design against user requirements. Research has produced a prototype of the LazisMu Umbulharjo application with the main features of a dashboard for managing data and general information and managing a charity box. User management, charity box location management, and finally the determination of the pick-up route. The application prototype has been tested for usability and calculated using the System Usability Scale (SUS) with an average score of 82. Based on this score, the prototype of the LazisMu Umbulharjo application can be accepted by users (ACCEPTABLE) with grade A and gets an EXCELLENT level